Computational Evaluation on the Interactions of an Opaque-Phase ABC Transporter Associated with Fluconazole Resistance in Candida albicans, by the Psidium guajava Bio-Active Compounds - Mithil Vora; Smiline Girija Aseervatham Selvi; Shoba Gunasekaran; Vijayashree Priyadharsini Jayaseelan (Korean Pharmacopuncture Institute, 2024)
Objectives: Candida albicans is an opportunistic pathogen that occurs as harmless commensals in the intestine, urogenital tract, and skin. It has been influenced by a variety of host conditions and has now evolved as a resistant strain. The aim of this study was thus detect the fluconazole resistant C. albicans from the root caries specimens and to computationally evaluate the interactions of an opaque-phase ABC transporter protein with the Psidium guajava bio-active compounds. Methods: 20 carious scrapings were collected from patients with root caries and processed for the isolation of C. albicans and was screened for fluconazole resistance. Genomic DNA was extracted and molecular characterization of Cdrp1 and Cdrp2 was done by PCR amplification. P. guajava methanolic extract was checked for the antifungal efficacy against the resistant strain of C. albicans. Further in-silico docking involves retrieval of ABC transporter protein and ligand optimization, molinspiration assessment on drug likeness, docking simulations and visualizations. Results: 65% of the samples showed the presence of C.albicans and 2 strains were fluconazole resistant. Crude methanolic extract of P. guajava was found to be promising against the fluconazole resistant strains of C. albicans. In-silico docking analysis showed that Myricetin was a promising candidate with a high docking score and other drug ligand interaction scores. Conclusion: The current study emphasizes that bioactive compounds from Psidium guajava to be a promising candidate for treating candidiasis in fluconazole resistant strains of C. albicans However, further in-vivo studies have to be implemented for the experimental validation of the same in improving the oral health and hygiene.